Delayed wave of c-Fos expression in the dorsal hippocampus involved specifically in persistence of long-term memory storage - Katche, Cynthia Lorena (2010)
Memory formation is a temporally graded process during which transcription and translation steps are required in the first hours after acquisition. Although persistence is a key characteristic of memory storage, its mechanisms are scarcely characterized. Here, we show that long-lasting but not short-lived inhibitory avoidance long-term memory is associated with a delayed expression of c-Fos in the hippocampus. Importantly, this late wave of c-Fos is necessary for maintenance of inhibitory avoidance long-term storage. Moreover, inhibition of transcription in the dorsal hippocampus 24 h after training hinders persistence but not formation of long-term storage. These findings indicate that a delayed phase of transcription is essential for maintenance of a hippocampus-dependent memory trace. Our results support the hypothesis that recurrent rounds of consolidation-like events take place late after learning in the dorsal hippocampus to maintain memories.